HEMATO-BIOCHEMICAL PROFILING OF A BURROWING CRAB EXPOSED TO POLYSTYRENE MICROPLASTIC CONTAMINANT (FUDMA JOURNAL OF SCIENCES, 2020)
The study evaluated the effect of polystyrene microplastic contaminant on hemato-biochemical parameters of Cardiosoma guanhumi from the mangrove area of Lagos Lagoon using standard methods. Total Haemocyte Count (THC) ranged between 3050.00±0.00 mL and 4200.00 ±0.05 mL with control crabs having the highest value of 4200.00±0.05 mL. There was significant difference between the treatment groups and the control (p
Keywords: Microplastic Contaminant, Land Crab, Pollution, Lagos Lagoon, Nigeria.